Early life environmental antibiotic exposure and preschool allergic diseases: A biomonitoring-based prospective study in eastern China - Zheng, Hang; Zeng, Xinxin; Xie, Qiuling; Wu, Yuhang; Liu, Quanhua; Chen, Qian; Huang, Lisu; Zhang, Weixi (Frontiers in Public Health, 2022)
Background Globally, the prevalence of allergic diseases remains high, as does the level of environmental antibiotics. It has been found that clinical antibiotic application may increase preschool allergy risk. However, few biomonitoring studies have been conducted about the association between early life environmental trace dose antibiotic exposure and preschool allergy. Objective To analyze the association between prenatal environmental antibiotic levels and allergic diseases using logistic regression models. Methods A total of 743 pregnant women and their offspring from the Shanghai Allergy Birth Cohort completed five years follow-up, and 251 mother-infant pairs were finally included. Maternal urine samples were collected for 15 antibiotic quantitative measurements using liquid chromatography-tandem mass spectrometry. The high-antibiotic group was defined as having at least half of antibiotics exceeding the median concentration. Allergic diseases were assessed by clinicians through clinical history, standardized questionnaires, and annual physical examinations until the age of five. Skin-prick-test (SPT) was performed at 5 years old. Results The incidence of allergic diseases was generally higher in the high-antibiotic than that in the low-antibiotic group. Compared to the low-comprehensive antibiotic group, children in the high-antibiotic group were weakly associated with allergic diseases but had a 6-fold increased risk of food allergens sensitivity (OR: 7.09, 95% CI: 1.59, 31.74). Association of above-median single prenatal antibiotic concentration exposure and allergic diseases was also observed (azithromycin and asthma, OR: 2.72, 95% CI: 1.15, 6.42; enrofloxacin and wheeze, OR: 2.22, 95% CI: 1.22, 4.05; trimethoprim and atopic dermatitis, OR: 2.00, 95% CI: 1.08, 3.71). Moreover, children with higher prenatal norfloxacin levels were more sensitive to food allergens (OR: 5.52, 95%CI: 1.54, 19.71). Conclusion Early-life environmental antibiotic exposure may be correlated with an increased risk of asthma, wheeze, atopic dermatitis, and SPT positivity for food allergens in 5-year-old children.